Evaluation of pH of bathing soaps and shampoos for skin and hair care - Jose Tarun; Jose Susan; Jacob Suria; Veronica John Susan; Sebastian Criton (Wolters Kluwer Medknow Publications, 2014)
Background: Normal healthy skin has potential of hydrogen (pH) range of 5.4-5.9 and a normal bacterial flora. Use of soap with high pH causes an increase in skin pH, which in turn causes an increase in dehydrative effect, irritability and alteration in bacterial flora. The majority of soaps and shampoos available in the market do not disclose their pH. Aims and Objectives: The aim of this study was to assess the pH of different brands of bathing soaps and shampoos available in the market. Materials and Methods: The samples of soaps and shampoos were collected from shops in the locality. The samples of different brands are coded before the analysis of the pH. Solution of each sample was made and pH was measured using pH meter. Results: Majority of the soaps have a pH within the range of 9-10. Majority of the shampoos have a pH within the range of 6-7. Conclusions: The soaps and shampoos commonly used by the population at large have a pH outside the range of normal skin and hair pH values. Therefore, it is hoped that before recommending soap to patient especially those who have sensitive and acne prone skin, due consideration is given to the pH factor and also that manufacturers will give a thought to pH of soaps and shampoos manufactured by them, so that their products will be more skin and hair friendly.